The partition of nutrients between mother and conceptuses in the pregnant rat - Frazer, J. F. D. (1970)
1. Diminishing the food supply to pregnant rats was associated with a subnormal degree of foetal loss among the larger litters, but a greatly lowered intake increased this foetal loss. 2. Whether the food intake was lowered, normal or increased, the increase in conceptus weight over the last half of pregnancy could be related to the total maternal weight increase over this period by the formula y = ¼x + 4·5n, where n was the number of foetuses. 3. With values of x below 20 g, this no longer held, but y never fell below 4·5 (n + 1). 4. It is concluded that Hammond's theory of the partition of nutrients is confirmed, so far as mother and conceptuses are concerned, in the rat.